Pregled vidnejših besedil v razdobjih literarnozgodovinskega razvoja sodobne slovenske mladinske fantastične pripovedi - Artnik, Gregor (Revija za elementarno izobraževanje, 2012)
An overview of prominent literary works in the period of literary and historical development of the Slovenian fantastic tale for youth. This article deals with contemporary Slovenian fantastic tale for youth and its development from the nineteen-thirties to the first decade of the present millennium. The purpose of the survey is not only to improve the transparency in the field of such literary texts, but also to present a certain literary and historical overview regarding the classification and the emergence of classic fantastic tale, fantasy and science fiction narratives for youth in Slovenia.
Keywords: contemporary fantastic tale for youth; fantasy narrative; genre syncretism; fantastic literature; Slovenian young adult literature